Relación diámetro - altura total - amplitud de copa de las plantas de Cedrelinga cateniformis Ducke con diferentes dosis de fertilización foliar en plantación. Puerto Almendra, Loreto, Perú - 2021 - Chu Ushihua, Mayra Alejandra (2022)
The thesis was carried out at the CIEFOR Puerto Almendra – FCF - UNAP facilities, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of relationship between the diameter, total height and width of the crown in the plants of Cedrelinga cateniformis Ducke "tornillo" with different doses of foliar fertilization in plantation, Puerto Almendra, Loreto, Peru - 2021. The variables used were the diameter, total height and width of the crown of the species under study; The foliar fertilization doses were dose 1 (20 ml of the compound/20,000 ml of water) and dose 2 (60 ml of the compound/20,000 ml of water). The results indicate that there is an excellent relationship between diameter - total height and crown width for Cedrelinga cateniformis Ducke "tornillo" plants; the allometric power and cubic models had a better fit for the diameter-total height ratio; for the diameter - crown width relationship, it was the cubic model and for the crown width - total height relationship, it was the composite model.